Zoonotic Rickettsia Species in Small Ruminant Ticks From Tunisia - Belkahia, Hanène; Selmi, Rachid; Zamiti, Sayed; Daaloul-Jedidi, Monia; Messadi, Lilia; Ben Said, Mourad (Frontiers in Veterinary Science, 2021)
Tick-borne rickettsioses present a significant public health threat among emerging tick-borne diseases. In Tunisia, little is known about tick-borne Rickettsia pathogens. Therefore, the aim of this study was to investigate the presence of Rickettsia species in small ruminant ticks from Tunisia. Adult ticks (n=694) were collected from goats and sheep in northern Tunisia. Obtained ticks were identified as Rhipicephalus turanicus (n=434) and Rhipicephalus sanguineus sensu lato (n=260). Selected ticks (n=666) were screened for the presence of Rickettsia spp. by PCR targeting a partial sequence of the ompB gene followed by sequence analysis. Rickettsial DNA was detected in 122 (18.3%) tested tick samples. The infection rates in Rh. turanicus and Rh. sanguineus s.l. ticks were 23.4% and 9.5%, respectively. The overall prevalence of rickettsial DNA was markedly higher in ticks collected from goats (23.2%) compared to those infesting sheep (7.9%). The detection of rickettsial DNA was significantly higher in ticks from the governorate of Beja (39.0%) than those from the governorate of Bizerte (13.9%). Two additional genes, the outer membrane protein A gene (ompA) and the citrate synthase gene (gltA), were also targeted for further characterization of the detected Rickettsia species. Genotyping and phylogenetic analysis based on partial sequences (n=106) of the three different genes revealed that positive ticks are infected with different isolates of two Spotted Fever Group (SFG) Rickettsia, namely Rickettsia massiliae and Rickettsia monacensis, closely related to those infecting camels and associated ticks from Tunisia, and humans and small ruminant ticks from neighboring countries like Italy, France and Spain.